Evaluation of the requirement for passenger car parking spaces using multi-criteria methods - Palevičius, Vytautas; Paliulis, Gražvydas Mykolas; Venckauskaitė, Juratė; Vengrys, Boleslovas (Journal of Civil Engineering and Management, 2013)
The present situation shows that the parking infrastructure in residential areas of Vilnius does not satisfy the existing level of motorization. Every evening people come home from work and end up parking cars on lawns, cycle and pedestrian paths, playgrounds, fire accesses and etc. In Lithuania, this problem emerged with the growing number of cars. There have been attempts to address parking shortage issues 20–30 years ago by building metal above-ground garages and underground car parks; but such solutions focused on existing burning needs alone. As a result, the current parking situation in residential areas is chaotic. This problem stems from the ineffectiveness of responsible institutions, which maintain the status quo. Consequently – as no car parking development projects are planned and implemented as well as no required statistical data is collected regarding conditions of car parking and etc. – people are forced to look for a solution by themselves, thus end up parking on lawns or playgrounds. This article aims to apply multi-criteria solutions (Multiple Criteria Decision Making – MCDM), which would allow indicating the worst passenger car parking conditions in residential areas from the social, economic and environmental points of view. Besides, it pursues identifying and substantiating the choice of territories that require the development of car parking solutions.